2006
DOI: 10.1017/s0950268806007175
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic influenza and vitamin D

Abstract: In 1981, R. Edgar Hope-Simpson proposed that a 'seasonal stimulus' intimately associated with solar radiation explained the remarkable seasonality of epidemic influenza. Solar radiation triggers robust seasonal vitamin D production in the skin; vitamin D deficiency is common in the winter, and activated vitamin D, 1,25(OH)2D, a steroid hormone, has profound effects on human immunity. 1,25(OH)2D acts as an immune system modulator, preventing excessive expression of inflammatory cytokines and increasing the 'oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
712
2
25

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 922 publications
(779 citation statements)
references
References 98 publications
14
712
2
25
Order By: Relevance
“…71 In other studies, a role for 25OHD in counteracting infection in the upper respiratory tract has been proposed. 72,73 These observations were based in part on epidemiological data linking seasonal variations in vitamin D status with the seasonality of infections such as influenza, 72 as well as randomized clinical studies demonstrating protective effects of vitamin D supplementation against colds and influenza. 73 Unlike the model described for tuberculosis, a mechanism by which vitamin D can combat respiratory infection due to colds or influenza has yet to be proposed; however, in view of the fact that cathelicidin has been shown to exhibit antiviral properties, 74 it is exciting to speculate that vitamin D therapy may provide a novel strategy for preventing these prevalent clinical problems.…”
Section: Vitamin D and Infectionmentioning
confidence: 99%
“…71 In other studies, a role for 25OHD in counteracting infection in the upper respiratory tract has been proposed. 72,73 These observations were based in part on epidemiological data linking seasonal variations in vitamin D status with the seasonality of infections such as influenza, 72 as well as randomized clinical studies demonstrating protective effects of vitamin D supplementation against colds and influenza. 73 Unlike the model described for tuberculosis, a mechanism by which vitamin D can combat respiratory infection due to colds or influenza has yet to be proposed; however, in view of the fact that cathelicidin has been shown to exhibit antiviral properties, 74 it is exciting to speculate that vitamin D therapy may provide a novel strategy for preventing these prevalent clinical problems.…”
Section: Vitamin D and Infectionmentioning
confidence: 99%
“…Cannell et al (2006) hypothesized that epidemic influenza is largely seasonal because of the annual cycle of solar UVB and vitamin D production. Two RCTs have supported this hypothesis (Urashima et al, 2010 and references therein).…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Papers outlining the evidence for vitamin D in reducing the burden of diseases with the highest mortality rates for which vitamin D reduces incidence and mortality rates include those for CVD (Parker et al, 2010), cancer , bacterial and viral respiratory infections (Cannell et al, 2006;Liu et al, 2007), chronic obstructive pulmonary disease (COPD; Black and Scragg, 2005), tuberculosis (TB; Liu et al, 2007), diabetes (Parker et al, 2010;Pittas et al, 2010), musculoskeletal diseases leading to falls (Cauley et al, 2008;Pfeifer et al, 2009) and dementia (Grant, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…It was also suggested that solar radiation degrades influenza virus [1]. Finally, it was also described that solar radiation triggers robust seasonal vitamin D production in the skin, and because of vitamin D’s known anti-infective/immune modulating properties, the consequence of vitamin D deficiency in winter months may mediate increased seasonal influenza epidemics [17]. …”
Section: Discussionmentioning
confidence: 99%